2005
DOI: 10.1111/j.1600-051x.2004.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the receptor of advanced glycation end products in gingival tissues of type 2 diabetes patients with chronic periodontal disease: a study utilizing immunohistochemistry and RT‐PCR

Abstract: Although there was no change in the staining intensity for RAGE between both groups, the increase in the mRNA for RAGE in the type 2 diabetes gingival epithelium may indicate a possible involvement of this receptor in the periodontal destruction in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 22 publications
5
127
0
5
Order By: Relevance
“…Importantly, the beneficial effects of RAGE blockade were paralleled by suppressed expression of the receptor and its ligands in gingival tissues and were independent of the level of glycaemia. Increased RAGE expression was subsequently reported in other experimental models of diabetes-associated periodontitis (Chang et al 2012a,b, Claudino et al 2012) and in gingival tissues of diabetic individuals with periodontitis, and its expression was correlated to that of NF-kB (Katz et al 2005, Abbass et al 2012, Yu et al 2012. These findings demonstrated that AGE-RAGE interaction may lead to the exaggerated inflammatory response and periodontal tissue destruction seen in diabetes.…”
Section: Hyperglycaemia and Cellular Stresssupporting
confidence: 57%
“…Importantly, the beneficial effects of RAGE blockade were paralleled by suppressed expression of the receptor and its ligands in gingival tissues and were independent of the level of glycaemia. Increased RAGE expression was subsequently reported in other experimental models of diabetes-associated periodontitis (Chang et al 2012a,b, Claudino et al 2012) and in gingival tissues of diabetic individuals with periodontitis, and its expression was correlated to that of NF-kB (Katz et al 2005, Abbass et al 2012, Yu et al 2012. These findings demonstrated that AGE-RAGE interaction may lead to the exaggerated inflammatory response and periodontal tissue destruction seen in diabetes.…”
Section: Hyperglycaemia and Cellular Stresssupporting
confidence: 57%
“…Conversely, the presence of MetS or any of its components in a previously periodontally healthy person could facilitate a prooxidant state which would diminish anti-oxidant capacity of the periodontal tissues, and the response of these tissues to bacterial challenge could be impaired. The presence of a high RAGE expression in periodontal tissues (Katz et al, 2005) is an important finding supporting the sensitivity of these tissues to products derived from oxidative damage. Moreover, AGE may promote apoptosis in osteoblasts (Alikhani et al, 2007a) and fibroblasts (Alikhani et al, 2007b), and this might have an influence on alveolar bone homeostasis and the progression of periodontitis.…”
Section: Resistin and Periodontitismentioning
confidence: 99%
“…The receptor for AGE (RAGE),an integral membrane protein, forming the central binding site on the cell surface for AGEs, is a multi ligand and signal transduction receptor belonging to immunoglobulin superfamily and can be unregulated under various pathological conditions (Katz et al 2005;Ziyadeh et al 1997;Park et al 2004;Schmidt et al 2000). The engagement of AGEs to RAGE leads to the activation of the transcription factor, nuclear factor kappa B (NFkB) and subsequent expression of NFkB regulated cytokines.…”
Section: Resultsmentioning
confidence: 99%